Preparation of Hydroxyapatite Scaffold using Luffa Cylindrica Sponge as Template - Fadli, Ahmad; Widiyanti, Prihartini; Noviana, Deni; Prabowo, Agung; Ismawati, Heni (Jurnal Rekayasa Kimia & Lingkungan, 2020)
Hydroxyapatite (HA) scaffold has been widely applied in the biomedical field especially for bone implants. The purpose of this research is to determine the influence of dispersant addition and stirring time on HA scaffold which formed using gambas sponges as a template. HA slurry was made by mixing 10 grams of HA, 12 grams of aquadest, 0,2; 0,25; 0,3 grams of Darvan 821A and 1 gram of sago. The slurry was impregnated into Luffa cylindrica sponges. The sample then dried at 110oC for 3 hours. The green bodies were burned at 600oC for 1 hour and followed by sintering at 1250oC for 1 hour. The results showed that the addition of dispersant and increasing of stirring time lead to smaller porosity and shrinkage. In addition 0,2; 0,25; and 0,3 grams dispersant, the resulting porosity in the range of 63,85-70,78%; 58,74-70,35%; and 53,42-69,66%. Shrinkage 39,43-53,71%; 27,75-50,68%; and 13,61-41,25%. Compressive strength 0,61-1,05 MPa; 2,88-3,81MPa; and 0,52-2,96 MPa. The macroporous and microporous average pore sized was 50 m dan 5 m.